Integrated Power-Line and Visible-Light Communications - van Manen, Corban (Wellington Faculty of Engineering Symposium, 2023)
The current state of the world places an important role on communication, specifically the different mediums for communication and how we can exploit them. The issue with such mediums is that very often, there are clear disadvantages that cause them to become less viable in certain conditions. For this project, an existing VLC (Visible Light Communication) device has shown to produce high speed communications across an unblocked path of visible light. The motivation for this project stems from the fact that although a VLC device has clear advantages such as a lack of consideration of frequency bands, non-licensed communication and a lack of interruption from other sources, there are clear disadvantages as well. Specifically, the datastream is extremely sensitive to external light sources, and a direct line of unblocked site is required for communication. This project calls for an addition to be made in the form of a PLC (powerline communication) device to act as a complementary form of communication. PLC devices do not have the advantages of license and band free communication. However, they are resilient to light interference, and can operate in any conditions with a mains line by modulating, injecting, and demodulating data over said mains. This report details the development and more importantly results of the project, displaying data on several metrics of the filter system, as well as an emphasis on the development process and results of the PCB and device itself. Shortcomings and alternative results of the project are also discussed in place of metrics and results in the cases that said metrics and results could not be achieved or measured.